Knocking Down TMPRSS2-ERG Fusion Oncogene by siRNA Could be an Alternative Treatment to Flutamide - Giorgia Urbinati; Isabelle de Waziers; Mateja Slamiç; Tobias Foussignière; Hafiz M Ali; Didier Desmaële; Patrick Couvreur; Liliane Massaad-Massade (Elsevier, 2016)
Our purpose was to develop a new pharmacological approach for the treatment of prostate cancer (PCa), the most common neoplasia in men. Recently, we developed siRNA against the fusion oncogene TMPRSS2-ERG found in 50% of patients and showed an antitumoral activity in animal model. Herein, we want to compare or combine the developed siRNA to flutamide (FLU), one of the gold-standard treatment of PCa. Therefore, concomitant or subsequent association of FLU to siRNA TMPRSS2-ERG was performed in VCaP cells and in SCID mice bearing xenografted VCaP tumors. ERG, androgen receptor, cleaved-caspase-3 as well as phase 1 and 2 drug-metabolizing enzymes were investigated within tumors. We observed similar results in terms of TMPRSS2-ERG knock-down and cell viability impairment for all distinct schedules of administration. The association of siRNA TMPRSS2-ERG-squalene nanoparticles with flutamide displayed similar tumor growth inhibition as mice treated with siRNA TMPRSS2-ERG-squalene nanoparticles alone and was paralleled with modification of expression of ERG, androgen receptor, and cleaved-caspase-3. Phase 1 and 2 enzymes were essentially affected by FLU and reverted when combined with squalenoylated siRNA. In conclusion, these results confirm the therapeutic effectiveness of squalenoyl siRNA nanomedicine for PCa based on siRNA TMPRSS2-ERG.